Non-Coding Transcriptome Provides Novel Insights into the Escherichia coli F17 Susceptibility of Sheep Lamb - Weihao Chen; Xiaoyang Lv; Weibo Zhang; Tingyan Hu; Xiukai Cao; Ziming Ren; Tesfaye Getachew; Joram M. Mwacharo; Aynalem Haile; Wei Sun (Biology, 2022)
It has long been recognized that enterotoxigenic Escherichia coli (ETEC) is the major pathogen responsible for vomiting and diarrhea. E. coli F17, a main subtype of ETEC, is characterized by high morbidity and mortality in young livestock. However, the transcriptomic basis underlying E. coli F17 infection has not been fully understood. In this study, RNA sequencing was performed to explore the expression profiles of circRNAs and miRNAs in the jejunum of E. coli F17-antagonism (AN) and -sensitive (SE) lambs. A total of 16,534 circRNAs and 271 miRNAs (125 novel miRNAs and 146 annotated miRNAs) were screened, and 214 differentially expressed (DE) circRNAs and 53 DE miRNAs were detected between the AN and SE lambs (i.e., novel_circ_0025840, novel_circ_0022779, novel_miR_107, miR-10b). Functional enrichment analyses showed that source genes of DE circRNAs were mainly involved in metabolic-related pathways, while target genes of DE miRNAs were mainly enriched in the immune response pathways. Then, a two-step machine learning approach combining Random Forest (RF) and XGBoost (candidates were first selected by RF and further assessed by XGBoost) was performed, which identified 44 circRNAs and 39 miRNAs as potential biomarkers (i.e., novel_circ_0000180, novel_circ_0000365, novel_miR_192, oar-miR-496-3p) for E. coli infection. Furthermore, circRNA-related and lncRNA-related ceRNA networks were constructed, containing 46 circRNA-miRNA-mRNA competing triplets and 630 lncRNA-miRNA-mRNA competing triplets, respectively. By conducting a serious of bioinformatic analyses, our results revealed important circRNAs and miRNAs that could be potentially developed as candidate biomarkers for intestinal inflammatory response against E. coli F17 infection; our study can provide novel insights into the underlying mechanisms of intestinal immunity.